Hacking in the public interest: Authority, legitimacy, means, and ends. (April 2016) - Powell, Alison
The cultural appropriation of ideas about hacking and opening knowledge have had significant impact on ways of developing participation in creating public interest knowledge and knowledge commons. In particular, the ideal of hacking as developed through studies of free and open source (F/OS) has highlighted the value of processes of participation, including participatory governance, in relation to the value of expanded accessibility of knowledge, including knowledge commons. Yet, these means and ends are often conflated. This article employs three examples of projects where hacker-inspired perspectives on scientific knowledge conflict with institutional perspectives. Each example develops differently the relationships between means and ends in relation to authority and legitimacy. The article's analysis suggests that while hacker culture's focus on authority through participation has had great traction in business and in public interest science, this may come limit the contribution to knowledge in the public interest - especially knowledge commons.